The package [videorecording (DVD)] - Davis, Andrew, 1946-; Hackman, Gene; Cassidy, Joanna, 1945-; Jones, Tommy Lee, 1946- (MGM DVD., 2000)
When Sgt. Johnny Gallagher is assigned the task of delivering a military prisoner to the U.S. for court martial, little does he know that they will be assaulted, and his prisoner will disappear. Gallagher soon finds a trail of clues leading to an international conspiracy- one that will change the course of mankind.